Consumer Attitude towards Organic Foods: A Multigroup Analysis across Genders - Evrim Erdoğan Yazar; Murat Burucuoğlu (Istanbul Business Research (IBR), 2019)
Environmental pollution, modern farming practices and animal transmitted diseases have led consumers to have food safety and health concerns regarding organic foods. This research aims to examine the relationship between consumers' health consciousness, food safety concerns, attitudes towards organic products, and intention to purchase organic food products. For this purpose, we first developed a research model; then, we tested the research model based on gender differences. According to the results of the research, the attitude toward organic food is a powerful indicator of the consumer's intention to purchase organic food. Health consciousness, food safety concerns, attitudes, and intentions have a significant relationship with each other. As a result of the gender based binary model comparison, the attitudes and intentions of male and female consumers towards organic food are different. Participants' increased awareness of health consciousness and food safety concerns increase the relevance of organic products, and has an impact on the development of the organic product market.
Keywords: 650; Health consciousness; Food safety concern; Organic food; Attitude; Gender